A study on the determinants of non-performing loan emphasizing on the macroeconomic variables focusing on the NBFIs of Bangladesh - Sinha, Rezwan Ahsan (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.